Análise e mapeamento das áreas verdes da cidade de Cuiabá – MT, utilizando imagens de alta resolução espacial - Caldas, Jonathan Anderson de Paula (2014)
Green areas exert numerous functions in the natural environment, especially in the urban environment, as in the context of cities, are important for the welfare of the population, contributing to improve the quality of life in the following areas: recreation, landscaping and environmental preservation in addition to mitigating the sun's heat, absorb sound and increase humidity by evapotranspiration from plants. Therefore, this work aims to create spatial and quantitative data specifying concrete indices of the real situation existing green area within the city limits of the city of Cuiaba-MT, in 2010. The same will be developed through analysis, representation and geographical distribution with application of GIS techniques, using the Geographic Information System (GIS) to facilitate localization and mapping, as well as images of high-resolution satellites (World View II with 0.50 cm spatial resolution) using visual interpretation of the entire urban area. The severity of the natural environment becomes the present moment brings the urge to reflect on the consequences of disrespect towards the urban environment. Therefore, any action that minimizes such effects will be very significant. The information available in both the public power, as in academic, research essential to propose policies to reverse the situation detected in the city, were scattered and unsystematic. This framework emphasizes the need to create a model that enables creation establish an index of green areas for the city, which best served to the questions found here. This is the principle not eliminate all existing parks and gardens , but that identified the need to improve the current conditions of the parks , squares and gardens existing and establish new standards in the training of new green areas . These principles are evident in the initial objectives proposed creation of these free spaces, which may or may not insert as green areas.